Integrated analysis of gut microbiome and its metabolites in ACE2-knockout and ACE2-overexpressed mice - Song, Lini; Ji, Wenyi; Cao, Xi (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Aberrant activation of the classic renin angiotensin system (RAS) and intestinal micro dysbiosis adversely affect insulin resistance (IR), dyslipidemia, and other metabolic syndrome markers. However, the action of angiotensin-converting enzyme 2 (ACE2) and gut health in systemic homeostasis vary, and their interaction is not completely understood.Methods: We adopted a combinatory approach of metabolomics and fecal 16S rRNA analysis to investigate gut microbiota and metabolite in two different mouse models, ACE2 knockout (ACE2 KO) mice and the ACE2-overexpression obese mice.: 16S rRNA gene sequencing revealed ACE2 influences microbial community composition and function, ACE2 KO mice had increased deferribacteres, Alcaligenaceae, Parasutterella, Catenibacterium, and Anaerotruncus, with decreased SCFAs-producing bacteria (Marvinbryantia and Alistipes). In contrast, ACE2-overexpressed mice exhibited an increased antiinflammatory probiotic (Oscillospiraceae, Marinifilaceae, Bifidobacteriaceae) and the SCFAs-producing microbes (Rikenellaceae, Muribaculaceae, Ruminococcaceae, Odoribacter, Alistipes), and decreased Firmicutes/Bacteroidetes, Lactobacillaceae, Erysipelotrichaceae, Lachnospiraceae. Metabolome analysis indicated differential metabolites in ACE2 KO and ACE2-overexpression mice, especially the glucolipid metabolism-related compounds. Furthermore, correlation analysis between gut microbiota and metabolites showed a dynamic mutual influence affecting host health.Our study confirms for the first time that a significant association between ACE2 status and gut microbiome and metabolome profiles, providing a novel mechanism for the positive effect of ACE2 on energy homeostasis.